Decreasing Resource Utilization Using Standardized Clinical Assessment and Management Plans (SCAMPs). Issue 4 (April 2019) - Luther, Gaurav; Miller, Patricia E.; Mahan, Susan T.; Waters, Peter M.; Bae, Donald S.
Abstract : Background: Standardized clinical assessment and management plans (SCAMPs) are a novel quality improvement initiative shown to improve patient care, diminish practice variation, and reduce resource utilization. Unlike clinical practice guidelines, a SCAMP is a flexible algorithm that undergoes iterative updates based on periodic data collection and review. We recently implemented a SCAMP for the closed treatment of pediatric torus fractures. The purpose of this study is to analyze the effect of SCAMP implementation on resource utilization, practice variability, cost of care, and outcomes. Methods: This study was a retrospective review of prospectively collected data on 273 patients with pediatric torus fractures. The pre-SCAMP cohort included 116 subjects from 2008 to 2010. The SCAMP cohort included 157 subjects from 2011 to 2013. The pre-SCAMP cohort was treated according to the judgment of attending fellowship-trained pediatric orthopaedic surgeons. The SCAMP cohort was treated with a standardized algorithm including radiographs and splint application at initial presentation, with a single follow-up at 3 weeks. Patient demographics were analyzed to verify comparability between cohorts. Follow-up data including clinic visits, x-rays and practice variability was recorded. Costing analysis was conducted using time-derived activity-based costing methodology. Outcomes were compared using Poisson regression analysis. Incident rate ratios (IRR) with 95% confidence limits were estimated. Results: No differences in clinical results were observed between the pre-SCAMP and SCAMP cohorts, and all patients demonstrated return to baseline activity at final follow-up. Patient demographics were comparable across cohorts. The SCAMP cohort had a 48% reduction in clinic visits [IRR, 0.52; 95% confidence interval (CI), 0.44-0.60; P <0.001], 60% reduction in x-rays (IRR, 0.40; CI, 0.33-0.47; P <0.001), and a 23% reduction in x-rays per clinic visit (IRR, 0.77; 95% CI, 0.65-0.91; P <0.001). Furthermore, SCAMP implementation resulted in a 49% reduction in the overall cost of care. Conclusions: SCAMPs provide a novel alternative to CPGs to implement cost effective changes in Orthopaedic practice. For pediatric torus fractures, SCAMP implementation resulted in decreased practice variability, resource utilization, and overall cost of care while maintaining clinical outcomes. Level of Evidence: Level 3.